Impact of Vitamin K Administration on INR Changes and Bleeding Events Among Patients With Cirrhosis. (February 2016) - Meyer, Adam V.; Green, Melissa; Pautler, Heather M.; Korenblat, Kevin; Deal, Eli N.; Thoelke, Mark S.
Background: The efficacy of vitamin K in lowering an elevated INR in the setting of cirrhosis is not well established.Objectives: The purpose of this investigation is to determine the effect of vitamin K administration on the INR and bleeding eventsamong hospitalized patients with cirrhosis.Methods: This is a retrospective investigation of patients hospitalized at an academic institution from 2010 to 2012. Adults with an ICD9 code supporting cirrhosis were segregated into matched cohorts based on provision of vitamin K. Multivariable logistic regression of factors associated with INR decrease and bleeding events was completed.Results: The final matched cohort (n = 276) contained 130 patients who received vitamin K and 146 who did not receive this therapy. ICU care (adjusted odds ratio [AOR] = 2.91; 95% CI = 1.54-5.49; P = 0.01), receipt of a blood product (AOR = 2.40; 95%CI = 1.35-4.24; P = 0.03), and baseline INR > 1.6 (AOR = 1.72; 95% CI = 1.00-2.95; P = 0.05), but not vitamin K administration (AOR = 1.17; 95% CI = 0.66-2.08; P = 0.59), were associated with INR decrease. Bleeding events occurred more frequently among patients with a history of esophageal varices (AOR = 6.35; 95% CI = 1.21-33.4; P = 0.03), but vitamin K administration did not have an impact on these events (AOR = 4.90; 95% CI = 0.56-43.0; P = 0.15).Conclusions: Administration of vitamin K did not affect INR changes or bleeding events in this cohort of hospitalized patients with cirrhosis.